HARMONISASI PELAKSANAAN PENGATURAN PENATAAN RUANG KAWASAN PERDESAAN DALAM KONSEP TIGA KESATUAN PERLINDUNGAN BERKELANJUTAN - JT Pareke (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2017)
Abstract: The national development scenarios which tend to focus on the economic interest, especially in the raw material manufacturing and high technology industries, caused the agricultural sector as the neglected raw material.Accelerating development through industrial development scenarios without strengthening the agricultural sector is easily slumped and difficult to recover. The problems that arise are the increasing demand for food due to the increase of population, the narrowing of agricultural land ownership due to land conversion, and the processing of land that is not environmentally knowledgeable. Development of agricultural sector should be integrative through empowerment, agrarian reform, and food sovereignty agenda in the framework of spatial structuring of rural areas based on the protection of sustainable agricultural land. This agricultural development agenda contains the meaning that government regulates the policies to protect the independence of individuals and communities that have local wisdom to rebuild food selfsufficiencyand sovereignty, so that national development leads to the welfare of society as a whole. The need for harmonization of the regulation is done by integrating the necessity of sustainable agricultural landprotection, the protection and empowerment of farmers, the agenda of food sovereignty into integrated spatial arrangement planning, finally the land needs are met and the farms become sustainable, independent and prosperous farmers, national food needs are met and Indonesia is a sovereign food country.Keywords: harmonization, spatial arrangement, protection of sustaibaility